Floor finish removal pad assembly and method of removing floor finish

By using a floor finish removal pad assembly, which includes compressible backing pads and discontinuously arranged coated abrasive articles, solves the hazards and inefficiency of the use of chemical stripping agents in the prior art, achieving efficient floor finish removal without chemicals, reducing costs and contamination.

CN115087784BActive Publication Date: 2025-02-283M INNOVATIVE PROPERTIES CO
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202080090877.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-30
Filing Date
2020-12-21
Publication Date
2025-02-28
Estimated Expiration
2040-12-21

AI Technical Summary

Technical Problem

The prior art requires the use of chemical stripping agents when removing floor finishes. The process is dirty, odorous and potentially dangerous, and the chemical-free method is inefficient, making it difficult to effectively remove floor coatings.

Method used

A floor finish removal pad assembly is employed, which includes a compressible backing pad and a non-rigid coated abrasive article attached to which the abrasive article is contacted with the floor surface by contacting the abrasive article, and the contact steps are repeated to remove the floor finish, completely independent of chemical stripping agents.

Benefits of technology

It realizes efficient removal of floor finishes without chemical peeling agents, reduces labor costs and environmental pollution, and has a safer and cleaner process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115087784B_ABST
    Figure CN115087784B_ABST
Patent Text Reader

Abstract

This invention describes a floor finish removal pad assembly. It also describes a method for removing floor finishes using this assembly. Specifically, the floor finish removal pad assembly includes a compressible backing pad and a plurality of discontinuously arranged, non-rigid coated abrasives or a single discontinuously patterned, substantially co-extending coated abrasive. Methods using such floor finish removal pad assemblies can effectively remove floor finishes even without the use of chemical strippers.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] Protective floor finishes can become scratched, scuffed and worn when exposed to the elements and foot and commercial building traffic (e.g., carts). In order to reapply a floor finish, the floor finish must be removed to expose the bare substrate underneath. Corrosive chemicals are often required to soften the hard finish so that it can be removed by abrasion. Summary of the invention

[0002] In one aspect, the present disclosure relates to a floor finish removal pad assembly. Specifically, the floor finish removal pad assembly includes a compressible backing pad having a first major surface and a second major surface, and a plurality of discretely arranged non-rigid coated abrasive articles attached to the first major surface of the compressible backing pad.

[0003] In another aspect, the present invention relates to a method for removing floor finishes. Specifically, the method for removing floor finishes comprises contacting a plurality of discretely arranged non-rigid coated abrasive articles attached to a major surface of a compressible backing pad with a coated hard floor surface, and optionally repeating the contacting step. The contacting step is performed in the absence of an effective amount of a chemical stripper.

[0004] In another aspect, the present invention relates to a floor finish removal pad assembly. Specifically, the floor finish removal pad assembly includes a compressible backing pad having a first major surface and a second major surface, and a discontinuously patterned non-rigid coated abrasive article substantially coextensive with the compressible backing pad and attached to the first major surface of the compressible backing pad. BRIEF DESCRIPTION OF THE DRAWINGS

[0005] Figure 1 is a bottom plan view of an exemplary floor finish removal pad assembly including several exemplary shapes of coated abrasive articles.

[0006] Figure 2 is a schematic perspective view of an exemplary abrasive particle shape.

[0007] Figure 3 is a schematic elevation view of an exemplary system for removing floor finish using a floor finish removal pad assembly.

[0008] Figure 4 is a schematic plan view of an exemplary abrasive pattern. DETAILED DESCRIPTION

[0009] In the field of floor care, floor stripping refers to the complete removal of old wax, finishes, dirt and debris found on floors. Floor stripping is known to be one of the most time-consuming and labor-intensive tasks in the maintenance and care of floors, or even in the entire professional cleaning industry. Typically, a wax or floor finish is applied to the floor surface substrate to help keep the floor looking beautiful, shiny and free of scratches and stains. Typically, these finishes or waxes are applied in the form of multiple layers or coatings. However, over time, especially in situations of heavy foot or other traffic, these layers can wear away, become embedded with dirt or debris, and cannot be cleaned or restored through regular routine maintenance. In these cases, the floor finish or wax must be completely removed so that a new finish coat can be applied.

[0010] The conventional floor stripping process consists of four discrete steps. First, a floor finish stripping chemical is applied to the floor surface and left on for approximately ten minutes. Next, a floor stripping pad is used to abrade the loosened and / or softened floor finish. Third, the stripping solution, now contaminated with dirt and floor finish particles, must be removed from the floor. Finally, the exposed floor must be cleaned and dried before any floor finish is reapplied.

[0011] Chemical-free floor stripping methods are desirable due to the mess, odor, and potential hazards of conventional processes. However, current methods take multiple passes to remove even a single layer of floor coating. Considering that most floor coatings recommend multiple (e.g., two or four) coats, currently available chemical-free stripping solutions are impractical given the additional labor costs required.

[0012] The floor finish removal pad assemblies described herein are surprisingly effective in removing floor finish layers without the use of chemical floor strippers. In some embodiments, the floor finish removal pad assemblies utilize abrasive particles of a specific shape and arrangement. In some embodiments, the floor finish removal pad assemblies utilize a non-rigid coated abrasive article that is discontinuously placed on a compressible backing pad. All floor surfaces have some degree of unevenness, and such compressibility and non-rigidity can help these assemblies reach low points of uneven floors and remove floor finish coatings thereon.

[0013] Figure 1 is a bottom plan view of an exemplary floor finish removal pad assembly including several exemplary shapes of coated abrasive articles. The floor finish removal pad assembly 100 includes a compressible backing pad 110, optional mounting holes 112, and exemplary discretely arranged coated abrasive articles 120a, 120b, 120c, and 120d.

[0014] The floor finish removal pad 100 can be any overall shape and size. In some embodiments, if it is intended to be installed on a rotary machine, the floor finish removal pad 100 can be round or disc-shaped. In some embodiments, if it is intended to be installed on a square sander or orbital sander, the floor finish removal pad 100 can be rectangular or square.

[0015] The compressible backing pad 110 can also be any suitable shape, size and thickness. In some embodiments, the compressible backing pad can be any suitable thickness between, for example, 0.25 cm and 10 cm. A thickness of one inch is common (2.54 cm). In some embodiments, the compressible backing pad can have a standard size and shape for installation on existing floor cleaning and treatment equipment. For example, a 20-inch (50.8 cm) floor pad is common, but a size of 10 inches (25.4 cm) to 24 inches (60.96 cm) in diameter may be suitable for these applications.

[0016] The compressible backing pad 110 can be formed by any suitable one or more materials. In some embodiments, the compressible backing pad 110 is polyurethane foam rubber or natural latex foam rubber. In some embodiments, the compressible backing pad 110 is open-cell ethylene-vinyl acetate. Any compressible natural or polymeric material or their blends can be used. In some embodiments, the compressible backing pad is a bulky and resilient nonwoven pad. In these embodiments, the material itself for a specific nonwoven fiber does not need to be compressible, but the bulky and resilient pad can be configured to be compressible because the fiber can be flexed under stress. The fiber can include natural and synthetic fibers. In some embodiments, the fiber can be or include natural fibers (e.g., plant fibers, such as hemp, jute, etc.; animal hair fibers, such as pig hair), polyamides (e.g., nylon), polyesters (e.g., polyethylene terephthalate or polyethylene isophthalate), rayon, polyethylene, polypropylene, synthetic fibers, or combinations thereof. Synthetic fibers include polymers derived from natural sources, such as polylactic acid derived from corn. The fibers may be adhered to each other at the joints where they contact each other by a binder and / or by melt bonding.

[0017] The compressible backing pad 110 includes an optional mounting hole 112. The optional mounting hole may be any suitable size or shape and may be adapted or designed to enable the floor finish removal pad assembly 100 to be used or attachable to any desired floor treatment or maintenance machine.

[0018] The discontinuously arranged coated abrasive articles 120a, 120b, 120c, and 120d can be of any suitable shape and size, but in many embodiments, it is desirable that such coated abrasive articles fit completely within the area of ​​the compressible backing pad 110 when attached. As can be seen from the various shapes represented as 120a, 120b, 120c, and 120d, there are many possible suitable configurations. In some embodiments, the coated abrasive articles all have the same shape; in some embodiments, the coated abrasive articles have different shapes. In some embodiments, the coated abrasive articles have the same size or area; in some embodiments, the coated abrasive articles have different sizes or areas. Suitable shapes include circular, oval, elliptical, polygonal, square, rectangular, trapezoidal, rhombus, rhombus, and the like. Irregular, curved, and other shapes are also possible and may be suitable for certain applications. The coated abrasive articles are non-rigid, meaning that they have at least some degrees of freedom to bend reversibly without cracking or breaking. In some embodiments, the coated abrasive article may include a cloth or fabric backing, or a thin or flexible polymer backing. In some embodiments, the coated abrasive article may include a nonwoven or foam backing. In some embodiments, the coated abrasive article may be removably attached to a compressible backing pad and may include an adhesive or hook and loop (or other physical interlocking) mechanism for mounting.

[0019] The coated abrasive article is covered with or at least includes a plurality of abrasive grains. In some embodiments, the plurality of abrasive grains include a type of abrasive. In some embodiments, the plurality of abrasive grains include a blend of multiple abrasives or abrasives. In some embodiments, the plurality of abrasive grains include only one of abrasive grains of substantially the same shape. In some embodiments, the plurality of abrasive grains include abrasive grains of multiple shapes. Abrasive grains can be any of the abrasive grain materials described herein, such as aluminum oxide, ceramic aluminum oxide, heat-treated aluminum oxide, silicon carbide, eutectic aluminum oxide-zirconium oxide, diamond, cerium dioxide, titanium diboride, cubic boron nitride, boron carbide, garnet, flint, corundum, sol-gel derived abrasive grains, uniformly dense quartzite (novaculite), pumice (pumice), red iron powder (rouge), sand, corundum, sandstone, diatomite (tripoli), powdered feldspar, staurolite (staurolite), ceramic iron oxide, glass powder, steel particles and their blends. The abrasive coating may also include a resin. Exemplary resins suitable for use include melamine resins, polyester resins such as condensation products of maleic anhydride and phthalic anhydride and propylene glycol, synthetic polymers such as styrene-butadiene (SBR) copolymers, carboxylated-SBR copolymers, phenolic resins, polyesters, polyamides, polyureas, polyvinylidene chloride, polyvinyl chloride, acrylic acid-methyl methacrylate copolymers, acetal copolymers, polyurethanes, and mixtures and crosslinked forms thereof.

[0020] Shaped abrasive particles can be particularly useful in certain embodiments. Shaped abrasive particles can be molded abrasive particles that include shapes not found in abrasives of substantially randomized conventional origin. Shaped abrasive particles can also be more uniform in shape. Methods for making shaped abrasive particles are known and described, for example, in U.S. Pat. No. 8,142,531 B2 (Adefris et al.). Suitable shaped abrasive particles can be any suitable shape (combined with Figure 2 In some embodiments, the abrasive particles may be formed in an average or characteristic size (whether shaped or not) of 0.01 mm to 0.1 mm, 0.1 mm to 0.5 mm, 0.5 mm to 1 mm or 1 mm to 5 mm. In some embodiments, a plurality of abrasive particles may include a blend of various sizes. Abrasive particles may be mixed with any other component or mixed in any other component to form an abrasive slurry and coated on the backing, including spraying or roller coating. Lubricants or other additives may be incorporated or included.

[0021] In some embodiments, any of the abrasive particles described in connection with the discontinuous, non-rigid coated abrasive article may be present on any other portion of the floor finish removal pad assembly, such as on a compressible backing pad.

[0022] In some embodiments, a single coated abrasive article including a backing is coextensive or substantially coextensive with a compressible backing pad. The backing of a single coated abrasive article can be patterned to produce an abrasive region adjacent to an area without abrasive. For any of the above discontinuous coated abrasive articles, any suitable abrasive or combination of abrasives can be used.

[0023] Figure 2 2 is a schematic perspective view of exemplary abrasive particle shapes. The equilateral triangle abrasive particle shape 222a has faces that are approximately equilateral triangles. The right triangle abrasive particle shape 222b has faces that are approximately right triangles. Figure 2 The shapes of those depicted in the drawings may be particularly suitable for a particular type of floor finish, or may be generally suitable for a variety of floor finishes, and the shape may be selected based on the application and desired performance. In some embodiments, other shapes or modifications of the shapes represented herein may be used. For example, the sidewall length or angle may be modified.

[0024] Figure 3 is a schematic front view of an exemplary system for removing floor finish using a floor finish removal pad assembly. A floor device 330 is combined with a floor finish removal pad assembly 310 to remove floor finish from a coated floor 340. The floor device 330 can be an automatic scrubber. In some embodiments, the floor device 330 can be an orbital sander or a square sander. The floor device 330 is configured to help contact the floor finish removal pad assembly 310 against the coated floor 340. In some embodiments, contacting the floor finish removal pad assembly 310 against the coated floor 340 includes rotating the floor finish removal pad assembly. The coated floor 340 can be any coated hard surface, including vinyl composition tile (VCT), solid vinyl tile, stone floor, or any other suitable natural or artificial floor surface. Figure 3, the coated floor 340 is indicated by a break line to show that it can have any large or small size. The coated floor may also include any wax or floor coating or protectant, with any number of coatings (but typically less than ten layers). In some embodiments, contacting the floor finish removal pad assembly against the coated floor includes translating the floor finish removal pad assembly laterally relative to the coated floor. In some embodiments, contacting the floor finish removal pad assembly against the coated floor is performed in the absence of a chemical stripper. In some embodiments, contacting the floor finish removal pad assembly against the coated floor is performed in the absence of water. In some embodiments, the contacting step is optionally repeated. In some embodiments, less than 10 contacting steps are required to remove a 25 micron thick floor finish coating.

[0025] Example

[0026] Floor finish removal pad assembly samples were prepared by coating an abrasive on a film backing. Cutting and finish removal of test samples. Unless otherwise noted, all parts, percentages, ratios, etc. in the examples and the remainder of this specification are by weight. Unless otherwise noted, all other reagents were obtained or purchased from chemical suppliers such as Sigma-Aldrich Company, St. Louis, Missouri, or can be synthesized by known methods.

[0027] Table 1. Abbreviations of materials and reagents used in the examples .

[0028]

[0029]

[0030]

[0031] Example 1

[0032] Use a notched bar to continuously coat BACK 1 with MAKE 1 at a weight of 24 grains per 4" x 6" (10 x 15 cm) area.

[0033] MIN1 was applied to the continuously moving BACK1 using an electrostatic coater at a total mineral weight of 60 grains per 4" x 6" (10 x 15 cm) area. A second mineral, MIN4, was also applied using an electrostatic coater at a weight of 20 grains per 4" x 6" (10 x 15 cm) area.

[0034] The material was converted into lengths of approximately 40" long and placed in a batch oven. The oven was run at 175F for 30 minutes, 195F for 30 minutes, and 210F for 70 minutes.

[0035] The material was removed from the batch oven and passed through a roller coater, SIZE 1 was applied with a 75 cm paint roller at a coverage of 483 g / m2, and the resulting product was cured at 90°C for 60 minutes and then at 102°C for a further 8 hours.

[0036] Example 2

[0037] The samples prepared in Example 1 were repeated except that MIN2 was used instead of MIN1.

[0038] Example 3

[0039] The samples prepared in Example 1 were repeated except that MIN3 was used instead of MIN1.

[0040] Example 4

[0041] A- Preparation of Laminated Ring Backing

[0042] Laminated Ring Backing Raw Materials

[0043]

[0044] The grid was laminated to a layer of 72 g / m2 BOSTIK using an iron press for a contact time of about two seconds, thus forming a continuous film on the loop backing.

[0045] B- Preparation of phenolic resin

[0046] The components of the phenolic resin used to prepare the abrasive articles described herein are listed in Table 2.

[0047] Table 2. Composition and percentage of phenolic resin mixture .

[0048] Element weight% B7 55-75 U0 1-10 D1 0.005-0.02) GEO 0.0005-0.003 FIL2 10-20 SIC 1-10 COL 0.1-0.5 FIL5 1-5 ANT 1-10

[0049] The curable composition was prepared by blending B7 with U0, then adding D1, GEO, COL, SIC, FIL2, ANT and slowly adding FIL5 under shear, using a high shear blade between 600 rpm and 900 rpm under high speed dispersion until a homogeneous mixture was obtained.

[0050] C- Stencil printing process

[0051] A patterned 3 mil polyester template (eg, Figure 4 The curable composition B-phenolic resin is stenciled by contacting the backing and the stencil, applying the curable composition to the side of the stencil opposite to the backing, forcing the curable composition through the screen / stencil with a scraper mechanism, and then separating the stencil from the backing, leaving a coating of the curable composition on the backing, the amount of the curable composition applied is 100gsm, with a film thickness of 100 microns. Then, while the curable composition is still wet, a 50gsm blend of 70% AP180 and 30% MIN5 (Spellman SL 150) is electrostatically coated. The entire construction is then thermally pre-cured in an 80°C batch oven for 30 minutes and finally cured in a 103°C batch oven for four hours. During this final stage, the curable composition is cured, and BOSTIK melts, wicking down along the lines and screens of the ring backing, thereby reopening a plurality of original holes of the backing. In this case, at least 90% of the original holes are reopened.

[0052] Comparative Example 1 3M High Productivity Pad 7300 (obtained from 3M Company, St. Paul, Minnesota) St.Paul,MN)

[0053] Comparative Example 2 3M Black Release Pad 7200 (available from 3M Company, St. Paul, Minnesota)

[0054] Comparative Example 3 SCOTCH-BRITE Surface Treatment Pad Plus (available from 3M Company, St. Paul, Minnesota)

[0055] Test Results

[0056] 1. Schiefer Cut Test

[0057] The Schiefer cutting test was performed to evaluate the relative abrasiveness of the articles of the present invention. The test was performed in a manner generally similar to that described in U.S. Pat. No. 5,626,512 (Palaikis et al.). Examples 1-3 were laminated with a layer of hook material (Aplix 220 hooks) and then cut into circular pads (8.25 cm in diameter). 3M 96 scrubbing pads (purchased from 3M Company, St. Paul, Minnesota) were cut into circular shapes of the same size. The hook side of the article was attached to the 3M 96 scrubbing pad, and the entire assembly was then fixed to the drive plate of a Schiefer abrasion tester (purchased from Frasier Precision Company, Gaithersburg, Maryland). The workpieces were all about 10.16 cm in diameter and about 0.317 cm thick. The initial dry weight of each workpiece was recorded, and the workpiece was fixed to the lower turntable of the tester using double-sided foam tape. The test was conducted under a load of 2.26 kg for a total of 2,000 revolutions with water applied to the surface of the acrylic disc at a rate of 40-60 drops / minute. The test was stopped every 500 revolutions. The workpiece was dried and weighed. The weight loss of the acrylic disc during the test is given as the result (reported in grams) in Table 3. Examples showing higher weight loss have higher cutting rates.

[0058] Table 3 Schiefeer cutting test results: weight loss after every 500 cycles, in grams

[0059]

[0060]

[0061] 2. Floor finish removal test

[0062] The vinyl composition tile (VCT) floor test area was first stripped and then coated with 1 coat of Feature Floor Finish (available from Sealed Air, Charlotte, NC, 28273) at a rate of 2000 square feet per gallon, and after drying, 5 marking lines were drawn on each tile, and then 4 coats of Feature Floor Finish were applied on top of the marking lines and allowed to cure for 7 days before testing. Examples 1-4 were laminated with a layer of hook material (Aplix 220 hooks) and then cut into 3" x 9" (7.6 x 23 cm) strips and the hook side of 6 strips were attached to a 14" x 20" 3M red cushioned floor pad in 3 rows, and the entire assembly was mounted on a 14" x 20" (35.6 x 51 cm) square scrubber (EBG-20 / C PIVOT, available from Square Scrug Company (Square Scrub)). The square scrubber was moved back and forth over the tested tile. The number of passes was counted until 95% of the marking line was removed. The before and after count was 2 times. Table 4 shows the test results. The embodiment that required fewer passes to remove the 4 layers of feature floor finish was more effective.

[0063] Table 4 Floor finish removal test results

[0064] Example No. Number of passes to remove 4 layers of floor finish Example 1 3 Example 2 4 Example 3 10 Example 4 3 Comparative Example 1 16 Comparative Example 2 30 Comparative Example 3 40

[0065] Although the terms and expressions employed are used as terms of description rather than limitation, and it is not intended that the use of such terms and expressions exclude any equivalents of the features shown and described or portions thereof, it is recognized that various modifications within the scope of the embodiments of the present invention are possible. Therefore, it should be understood that although the present invention has been specifically disclosed through specific embodiments and optional features, modifications and variations of the concepts disclosed herein may be deduced by those of ordinary skill in the art, and such modifications and variations are considered to be within the scope of the embodiments of the present invention.

Claims

1. A floor finish removal pad assembly comprising: a compressible backing pad having a first major surface and a second major surface; and A plurality of discretely arranged non-rigid coated abrasive articles are attached to the first major surface of the compressible backing pad, wherein the coated abrasive articles include equilateral triangle-shaped particles or right-angled triangle-shaped particles.

2. The floor finish removal pad assembly of claim 1, wherein a plurality of discretely arranged non-rigid coated abrasive articles are removably attached to the first major surface of the compressible backing pad.

3. The floor finish removal pad assembly of claim 1, wherein the coated abrasive article further comprises aluminum oxide particles.

4. The floor finish removal pad assembly of claim 1, wherein the compressible backing pad is a lofty, nonwoven pad.

5. The floor finish removal pad assembly of claim 1, wherein the compressible backing pad is a foam pad.

6. The floor finish removal pad assembly of claim 1, wherein the compressible backing pad comprises abrasive particles.

7. The floor finish removal pad assembly of claim 1, wherein the coated abrasive article comprises a lubricant.

8. A method of removing floor finish, comprising: contacting a plurality of discretely arranged nonrigid coated abrasive articles attached to a major surface of a compressible backing pad with a coated hard floor surface; as well as optionally repeating the contacting step; wherein the contacting step is performed in the absence of an effective amount of a chemical stripper, and The coated abrasive article comprises equilateral triangle particles or right-angled triangle particles.

9. The method of claim 8, wherein the coated abrasive article further comprises aluminum oxide particles.

10. The method of claim 8, wherein the contacting step is also performed in the absence of water.

11. The method of claim 8, wherein less than ten contact steps are required to remove a 25 micron thick acrylic floor finish coating.

12. The method of claim 8, wherein prior to the contacting step, the method comprises attaching the compressible backing pad to a scrubber or sander.

13. The method of claim 12, wherein the compressible backing pad is attached to an automatic scrubber.

14. The method of claim 12, wherein the compressible backing pad is attached to an orbital sander.

15. A floor finish removal pad assembly comprising: a compressible backing pad having a first major surface and a second major surface; and A discontinuously patterned non-rigid coated abrasive article substantially coextensive with the compressible backing pad and attached to the first major surface of the compressible backing pad, wherein the coated abrasive article comprises equilateral triangle particles or right triangle particles.

16. The floor finish removal pad assembly of claim 15, wherein the coated abrasive article further comprises aluminum oxide particles.

17. The floor finish removal pad assembly of claim 15, wherein the compressible backing pad is a lofty nonwoven pad or a foam pad.

Citation Information

Patent Citations

  • Scouring articles and process for the manufacture of same

    US5626512A

  • Shaped abrasive particles with a sloping sidewall

    US8142531B2

  • Abrasive product, method of making and using the same, and apparatus for making the same

    CN1671510A

  • Abrasive product and method of making and using the same

    US20030207659A1

  • Polishing or grinding pad with multilayer reinforcement

    WO2019140086A1